The Palgrave Handbook of Urban Development Planning in Africa - Khayesi, Meleckidzedeck; Wegulo, Francis Nyongesa (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Where can one get a synthesis of research findings on urban development planning in Africa? This book addresses this gap in knowledge by distilling existing research to provide insights into theories, research designs, empirical findings and approaches on urban development planning in Africa. Starting with the overall planning culture and strategies, the book chapters move on to specific themes such as governance, population, poverty, water, recreation, transport, agriculture, air quality and rural-urban linkages. This book reduces the prevailing risk of unnecessary duplication of research and the inadequate attention that is being given to extending research in new areas. This situation has partly been due to existing research remaining scattered in different organizations and publications and has not been subjected to critical synthesis to unearth any new developments that it contains. The book makes available research findings to be utilized in current and future urban development planning in Africa. Meleckidzedeck Khayesi is a Human Geographer with specialisation in Transport Geography. His current research interests include sustainable transport and development, focusing on walking, cycling, road safety, public transport, transport policy, and spatial aspects of sustainable development. Francis Nyongesa Wegulo is retired Professor of Human Geography at Egerton University, Kenya. His research focus is on regional development, rural-urban linkages, role of small towns and market centres in local level development, informal sector and livelihoods, and urban development.
Chapter 1: Na.vigating the Urban Development Planning Landscape in Africa -- Chapter 2: Planning Cultures -- Chapter 3 : Political Management and Governance -- Chapter 4 : Agriculture -- Chapter 5 : Financial Resources -- Chapter 6 : Population Planning and Management -- Chapter 7 : Managing Poverty -- Chapter 8 : Public Transport Services -- Chapter 9 : Water Management -- Chapter 10 : Rural-urban Linkages -- Chapter 11 : Recreation Planning and Management -- Chapter 12 : Air Quality.
Keywords: Africa-Politics and government; Political science; Economic development; Human geography; African Politics; Political Science; Development Studies; Development Studies; Human Geography